(untitled) (Maʿālim al-Qurʾān wa al-Sunnah, 2020)
This paper discusses the munasaba (coherence) fasila (separator) of the related beautiful names of Allah in surah al-tawba which are mentioned in eighteen times. This study attempts at clarifying in particular the relation between the separator of beautiful names of Allah and the verses of surah al-tawba in its immediate context. On a broader level, the study aims to open the way to the relation between textual meanings and verse structures used to indicate them, and the separator that are determined by those relations. We will answer this subject through inductive method by collecting all separators of beautiful names of Allah in surah al-tawba and sort them in descending order. Next, application of the analytical and descriptive method aims at depicting the coherence and the relation between the separators and the selected verses. This study concludes that the occurrence of many separators of the beautiful names of Allah signified its importance and instructional purposes. Plus, all the separators are mentioned in jumla ismiyya (nominal sentence) showing their certitude in clearer and stronger way.